Computational modeling of flavor perception in complex food systems - Min Liu; Jinfeng Zhong; Xiong Liu; Pingping Shi; Xiaoli Qin (Journal of Food Engineering, 2027)

Systemic toxicity of thiamethoxam in the mud crab (Scylla paramamosain): Oxidative stress, neurotoxicity, and growth retardation - Zhennan Wang; Ye Sun; Kaiming Luo; Shaolin Yao; Ce Shi; Changkao Mu; Chunlin Wang; Pingping Zhan; Yangfang Ye (Environmental Pollution, 2026)

A charge and size-switchable Au2Pt nanosystem for deep-tumor penetration and combinatorial therapy of ocular uveal melanoma - Lingdan Kong; Linxin Chen; Pingping Huang; Linghong Wang; Kang Han; Xiaoqian Shi; Yue Zhang; Jizhen Wang; Yunhai Tu; Yuqin Wang; Yong Liu (Chemical Engineering Journal, 2026)

Machine learning for lithology identification in electrical image logging: A case study of the Chang 73 Sub-Member, Yanchang Formation, East Gansu region, Ordos Basin - Jiaqi Li; Hongping Bao; Shilong Liu; Pingping Shi; Feiming Gao; Liubin Wei; Langlang Wang; Hongyan Yu (Earth Science Informatics, 2026)

Dietary supplementation of Radix Isatidis polysaccharides improves meat quality in broilers by regulating lipid metabolism, antioxidant defense, and the gut-muscle axis - Wei Wang; Wenbin Ouyang; Haibo Xiao; Panpan Shi; Pingping Li; Jianguo Zeng; Meirong Song; Sundus Javed; Peng Huang (Research in Veterinary Science, 2026)

Species-specific environmental niches govern biogeographic patterns and seasonal dynamics of the harmful algal genus Phaeocystis in Chinese seas - Pingping Shen; Jiayi Shi; Xuejun Fu; Qingshang Song; Yue Xue; Xiyan Wang; Mengqi Dong; Haiping Li (Environmental Pollution, 2026)

Nitrogen doping engineering of Ru nanoparticles/Mo2C MXene for efficient hydrogen production via NH3BH3 hydrolysis - Zhenluo Yuan; Fei Ya; Yang Shi; Shuyan Guan; Pingping Wang; Pei Liu; Shiqian Zhao; Qiuming Peng; Yanping Fan; Baozhong Liu (Chemical Engineering Journal, 2026)

Dermal absorption and percutaneous penetration of p-phenylenediamines (PPDs) and p-phenylenediamine quinones (PPD-Qs): Mechanisms and implications for human dermal exposure risks - Wenyan Wang; Yuhao Cao; Yizhen Wang; Pingping Wang; Bin Liu; Shaohan Zhang; Yumeng Shi; Hongkai Zhu; Lei Wang; Yarui Liu; Zhipeng Cheng (Journal of Hazardous Materials, 2026)

Rational design of fermented mustard tuber quality: Transitioning from empirical processing to precision control via texture-flavor synergy and targeted fermentation strategies - Wenxin Chen; Xiaoli Qin; Pingping Shi; Jinfeng Zhong (Trends in Food Science & Technology, 2026)

Transcriptome Analysis Reveals the Mechanism by which Probiotic Alleviate the Response of Juvenile American Shad (Alosa sapidissima) to High Temperatures - Chuwen Qiu; Chubing Gao; Pingping Deng; Zhuo Sun; Yongshi Liu; Jiabo Xu; Yonghai Shi (Probiotics and Antimicrobial Proteins, 2026)

Cr-doped CeO2 enables wettability-matched Pt catalysts for nearly complete lignocellulose conversion - Pingping Lu; Weichao Chou; Jun Li; Nan Shi; Lunan Wu; Bin Lou; Jing Wu; Dong Liu (Journal of Environmental Chemical Engineering, 2026)

NaCl and light quality reprogram carbohydrate metabolism to modulate growth, quality, and flavor in mustard (Brassica juncea) sprouts - Hongmei Di; Ling Li; Liping Su; Lisha Peng; Ling Rao; Zhifeng Chen; Victor Hugo Escalona; Jing Yang; Yu'nong Zhou; Yong Li; Xuena Yu; Kehao Liang; et al. (Food Chemistry, 2026)

Vertical Distribution and Controls on Heavy Metal(loid)s in Shallow Fissure Soils of Karst Geochemical Background Regions - Liang Tai; Yong Niu; Jia Chen; Gang Li; Pingping Fan; Feng Zhang; Tingjun Tan; Kaiqian Shi (Water, Air, & Soil Pollution, 2026)

Group IIId ethylene responsive factor 34 as a positive modulator of ABA signal pathway in Arabidopsis - Li Zhang; Mingxin Piao; Luyao Ji; Zixun Gao; Pingping Wang; Zeng Zhou; Jinpeng Zou; Qingchi Shi; Fang Liu; Yuping Xie; Mingdi Bian; Zhenming Yang; et al. (Plant Science, 2026)

A Fiber-Driven Finite Element Model for Predicting Residual Limb Soft Tissue Deformation: Applications in Prosthetic Socket Design - Ling Wang; Ziyan Qiu; Lei Tang; Fuhao Huang; Pingping Wei; Senay Mihcin; Changning Sun; Hongyuan Zhao; Lei Shi; Song Han; Dichen Li (Annals of Biomedical Engineering, 2026)

Integrative Single-Cell Analysis Decodes Gene Expression and Chromatin Accessibility in the Developing Human Fetal Brain - Tiantian Xu; Huihui Tao; Lingling Zhou; Haiyan Yu; Shi Bai; Hui Guo; Zhipeng Zeng; Wei Shi; Chunmei Wen; Mengyao Wu; Xuejia Zheng; Pingping Ye; et al. (Molecular Neurobiology, 2025)

Effects of dietary Lactococcus lactis supplementation on growth performance, intestinal and water microbiota of juvenile American Shad (Alosa sapidissima) under high temperature - Chuwen Qiu; Pingping Deng; Yonghai Shi (World Journal of Microbiology and Biotechnology, 2025)

Single cell transcription revealing key transcription factors in embryonic kidney development - Jingxian Huang; Bing Yan; Hongwei Wu; Hougang Yang; Shaodong Luan; Haiyan Yu; Wei Shi; Pingping Ye; Fang Yuan; Qiang Yan; Fanna Liu; Lianghong Yin; et al. (Molecular and Cellular Biochemistry, 2025)

ATF4 regulates PI3K/AKT signaling axis to promote angiogenesis after myocardial infarction - Pingping He; Weirong Zeng; Jiao Li; Yu Zhang; Ranzun Zhao; Weiwei Liu; Yongchao Zhao; Zhijiang Liu; Changyin Shen; Wei Chen; Yan Wang; Bei Shi (In Vitro Cellular & Developmental Biology - Animal, 2025)

N6-methyladenosine reader YTHDF3-mediated CEBPA translation maintains genomic stability and stem cell function to prevent liver injury - Yaxu Liang; Weiwei Yu; Haifeng Sun; Dayu Wang; Zhibo Wang; Hailing Shi; Yang Cao; Zijie Zhang; Jun Liu; Zhongyu Zou; Jiangbo Wei; Tong Wu; et al. (Science China Life Sciences, 2025)

Temperature-dependent shell disease may relate to bacterial community changes of mud crab Scylla paramamosain in RAS - Kaijia Yu; Xiaopeng Wang; Chunlin Wang; Changkao Mu; Yangfang Ye; Pingping Zhan; Ronghua Li; Ce Shi (Aquaculture, 2025)

Polyploid breeding of Saccharina japonica: Harnessing aposporous reproduction - Pingping Tian; Yan Li; Nianchao Xue; Weiwei Wang; Shuxiu Chen; Yanling Liu; Juan Sun; Guangjin Liang; Juping Zhao; Liang Shi; Nan Zhao; Xia Li; et al. (Aquaculture, 2025)

Development and evaluation of high-throughput HD-Marker arrays in pacific white shrimp (Litopenaeus vannamei) - Mingyang Liu; Zhihui Yang; Xin Huang; Qifan Zeng; Qianqian Mu; Zhenyuan Xu; Zijian Li; Pingping Liu; Shi Wang; Jingjie Hu; Zhenmin Bao (Aquaculture, 2025)

Food-derived peptides as novel therapeutic strategies for NLRP3 inflammasome-related diseases: a systematic review - Ziqi Zhang; Yuan Zhang; Meiying Zhang; Chenfeng Yu; Pingping Yang; Minxuan Xu; Jitao Ling; Yuting Wu; Zicheng Zhu; Yixuan Chen; Ao Shi; Xiao Liu; et al. (Critical Reviews in Food Science and Nutrition, 2025)

Corrigendum to “Source and bioavailability of quaternary ammonium compounds (QACs) in dust: implications for nationwide exposure in China” [J Hazard Mater 480 (2024) 136268] - Yuhao Cao; Zhiguo Cao; Pingping Wang; Leicheng Zhao; Shaohan Zhang; Yumeng Shi; Lu Liu; Hongkai Zhu; Lei Wang; Zhipeng Cheng; Hongwen Sun (Journal of Hazardous Materials, 2025)

Spectral Analysis of Dissolved Organic Carbon in Seawater by Combined Absorption and Fluorescence Technology - Xuan Cao; Feng Xiong; Yang Wang; Haikuan Ma; Yanmin Zhang; Yan Liu; Xiangfeng Kong; Jingru Wang; Qian Shi; Pingping Fan; Yunzhou Li; Ning Wu (Journal of Marine Science and Engineering, 2024)
Dissolved organic carbon refers to soluble carbon substances in water bodies and can be used as an important indicator for water pollution. Spectroscopic detection is commonly used to detect dissolved organic carbon in seawater. However, independent spectral methods are susceptible to interference, and insufficient extraction of the data features can occur. Accordingly, this study introduces a multisource spectral fusion method that relies on a combination of principal component analysis and convolutional neural networks to construct the detection model. The Bayesian correction method is used for calibration, and the dissolved organic carbon content of 10 groups of unfiltered seawater samples is analyzed. Correcting the spectral data acquired from samples containing impurities significantly improved the linear correlation coefficient R2 of dissolved organic carbon from 0.8891 to 0.9838. Similarly, the mean absolute error was significantly reduced from 15.33% to 3.24%, while the individual absolute error was effectively controlled, remaining within 9%. The obtained results show that the developed method effectively integrates the ultraviolet absorption and fluorescence spectral data and overcomes interference from other substances using the Bayesian correction method. Overall, this provides a highly accurate detection system with potential applications in monitoring the marine environment.

Source and bioavailability of quaternary ammonium compounds (QACs) in dust: Implications for Nationwide Exposure in China - Yuhao Cao; Zhiguo Cao; Pingping Wang; Leicheng Zhao; Shaohan Zhang; Yumeng Shi; Lu Liu; Hongkai Zhu; Lei Wang; Zhipeng Cheng; Hongwen Sun (Journal of Hazardous Materials, 2024)

U(VI) sorption by CTAB/Bent–MOF-74 from various carbonate solutions - BingTao Gui; Jun Liu; Cheng Wang; Shilong Shi; Junxiang Shu; PingPing Ding; Juan Zhai; Changsong Zhao (Journal of Water Process Engineering, 2024)

Analysis of Tidal Current Energy Potential in the Major Channels of the Bohai Strait Based on Delft3D - Pengcheng Ma; Hongyuan Shi; Huaiyuan Xue; Pingping Li; Yongkang Sun (Journal of Ocean University of China, 2024)

Whether the development strategy of the Yangtze River Economic Belt can achieve the double welfare effects of synergistic governance of pollution control and carbon reduction? - Dongri Han; Pingping Sun; Caifeng Bi; Ziyi Shi (Urban Climate, 2024)

Edible composite films: enhancing the postharvest preservation of blueberry - Dongfang Shi; Boya Zhao; Pingping Zhang; Ping Li; Xinpei Wei; Kai Song (Horticulture, Environment, and Biotechnology, 2024)

Effect of liquid nitrogen spray quick-freezing technology on the quality of bamboo shoots, Dendrocalamus brandisii from Yunnan Province, China - Zhenmei Fan; Hui Shen; Tenggen Hu; Lijuan Yu; Yujuan Xu; Jijun Wu; Pingping Shi; Xianliang Song; Yuanshan Yu (Journal of Food Engineering, 2024)

Effects of dietary supplementation with Radix Isatidis polysaccharide on egg quality, immune function, and intestinal health in hens - Panpan Shi; Zenghao Yan; Miaofen Chen; Pingping Li; Deqin Wang; Junjuan Zhou; Zhaojie Wang; Shihao Yang; Zhikun Zhang; Chuyuan Li; Yulong Yin; Peng Huang (Research in Veterinary Science, 2024)

Incorporation of ascorbic acid and L-cysteine in sodium carboxymethyl cellulose coating delays color deterioration and extends the shelf-life of fresh-cut asparagus lettuce (Lactuca sativa var. angustata) - Renying Yu; Huibo Song; Yanan Chen; Nan Shi; Hui Shen; Pingping Shi; Huosheng Shu; Xiaoxue Kong; Lijuan Yu; Haibo Luo (Postharvest Biology and Technology, 2023)

Analysis of the evolution of the Yellow River Delta coastline and the response of the tidal current field - Lili Zhang; Hongyuan Shi; Hao Xing; Pingping Li; Pengcheng Ma (Frontiers in Marine Science, 2023)
The coastline of the Yellow River Delta has undergone continual alterations due to both natural forces and human activity. Studying these changes is crucial for promoting economic growth and preserving the region’s ecological balance. Based on imagery captured by the Landsat5 and Landsat8 satellites, this study uses statistical data from the Digital Shoreline Analysis System (DSAS), including Net Shoreline Movement (NSM), End Point Rate (EPR), and Linear Regression Rate (LRR), to analyze the changes in the Yellow River Delta coastline from 2009 to 2019. This being the case, a hydrodynamic model under different shoreline conditions was established using Delft3D to compare and analyze the impact of shoreline changes on the tidal current field. From 2009 to 2019, the coastline in the study area exhibited an average movement distance of 1285m (NSM) and an annual change rate of 127.7m/a (LRR). The average increase in the area of the current estuary was 7.68km 2 /a, while the average decrease in the area of the old estuary was 4.91km 2 /a. Shoreline evolution is primarily influenced by the influx of water and sediment into the ocean. Following the implementation of water and sediment regulation, the existing estuary’s shoreline experienced a rapid initial accumulation of silt, which subsequently decelerated over time. Conversely, the former estuary has consistently undergone erosion. The greater the change in shoreline, the closer to the coast, and the greater the change in the tide. From 2009 to 2019, flow velocity and direction in the Yellow River Delta generally showed a decreasing trend, with changes ranging from 0.34% to 25.94%. The residual flow velocity near the current estuary gradually increased by about 2cm/s, while that near the abandoned old estuary gradually decreased by about 1cm/s, with no significant changes offshore. The sediment transported by the Yellow River is deposited at the current estuary, causing the coastline to move northeastward. In the abandoned estuary, there is erosion, causing the coastline to retreat.

Numerical Simulation of the Beach Response Mechanism under Typhoon Lekima: A Case Study of the Southern Beach of Chudao - Hao Xing; Pingping Li; Lili Zhang; Huaiyuan Xue; Hongyuan Shi; Zaijin You (Journal of Marine Science and Engineering, 2023)
Typhoons play an important role in beach evolution. The storm surge and large waves caused by typhoons can cause significant changes in beach morphology in a short period of time. The mechanism of beach evolution and profile changes during typhoons is significantly different from that under non-typhoon dynamic conditions. The XBeach numerical model provides an effective tool for predicting the response of sandy coasts to typhoons. This study is based on field-collected long-term beach profile elevations and grain size data, which were used to establish a two-dimensional XBeach model for simulating the morphological evolution of Cudao Island Beach under Typhoon Lekima. The GSA (Generalized Sensitivity Analysis) method was used to determine the sensitivity order of several important parameters in this modeling. Four different moments of wave height variation were selected during the typhoon process to analyze and study beach evolution. The results show that Chudao South Beach is always in a state of erosion during the typhoon period. The wave water increase is apparent in the nearshore wave-breaking area. The beach shoulder in the northeastern part of the beach is short, and the profile, with a short length, responds quickly to the typhoon. The eroded sediment is mainly deposited in the lower part of the intertidal zone or even transported outside of the wave-breaking zone, and a small part is transported to the shore and deposited in the high-tide zone. The continuous sediment transport along the coast of Chudao Beach is an important factor that influenced the evolution of each profile during Typhoon Lekima.

High-titer production of myo-inositol by a co-immobilized four-enzyme cocktail in biomimetic mineralized microcapsules - Pingping Han; Chun You; Yunjie Li; Ting Shi; Hong Wu; Yi-Heng P. Job Zhang (Chemical Engineering Journal, 2023)

Jumping of flea beetles onto inclined platforms - Le Zong; Jianing Wu; Pingping Yang; Jing Ren; Guanya Shi; Siqin Ge; David L. Hu (Journal of Comparative Physiology A, 2023)

A global survey of organophosphate esters and their metabolites in milk: Occurrence and dietary intake via milk consumption - Shunying Yao; Zhixiong Shi; Pei Cao; Lei Zhang; Yu Tang; Pingping Zhou; Zhaoping Liu (Journal of Hazardous Materials, 2023)

Metagenomic insights into the changes in the rhizosphere microbial community caused by the root-knot nematode Meloidogyne incognita in tobacco - Peng Lu; Heli Shi; Jiemeng Tao; Jingjing Jin; Sujie Wang; Qingxia Zheng; Pingping Liu; Bikun Xiang; Qiansi Chen; Yalong Xu; Zefeng Li; Jun Tan; et al. (Environmental Research, 2023)

Selection Signatures of Pacific White Shrimp Litopenaeus vannamei Revealed by Whole-Genome Resequencing Analysis - Hao Wang; Mingxuan Teng; Pingping Liu; Mingyang Zhao; Shi Wang; Jingjie Hu; Zhenmin Bao; Qifan Zeng (Frontiers in Marine Science, 2022)
The Pacific white shrimp Litopenaeus vannamei is among the top aquatic species of commercial importance around the world. Over the last four decades, the breeding works of L. vannamei have been carried out intensively and have generated multiple strains with improved production and performance traits. However, signatures of domestication and artificial selection across the L. vannamei genome remain largely unexplored. In the present study, we conducted whole genomic resequencing of 180 Pacific white shrimps from two artificially selective breeds and four market-leading companies. A total of 37 million single nucleotide polymorphisms (SNPs) were identified with an average density of 22.5 SNPs/Kb across the genome. Ancestry estimation, principal component analysis, and phylogenetic inference have all revealed the obvious stratifications among the six breeds. We evaluated the linkage disequilibrium (LD) decay in each breed and identified the genetic variations driven by selection. Pairwise comparison of the fixation index ( F st ) and nucleotide diversity (θ π ) has allowed for mining the genomic regions under selective sweep in each breed. The functional enrichment analysis revealed that genes within these regions are mainly involved in the cellular macromolecule metabolic process, proteolysis, structural molecule activity, structure of the constituent ribosome, and responses to stimulus. The genome-wide SNP datasets provide valuable information for germplasm resources assessment and genome-assisted breeding of Pacific white shrimps, and also shed light on the genetic effects and genomic signatures of selective breeding.

Transcriptional Responses of Flavin-Containing Monooxygenase Genes in Scallops Exposed to PST-Producing Dinoflagellates Implying Their Involvements in Detoxification - Lingling Kong; Pingping Liu; Moli Li; Huizhen Wang; Jiaoxia Shi; Jingjie Hu; Yueru Li; Xiaoli Hu (Frontiers in Marine Science, 2021)
Flavin-containing monooxygenase (FMO) is one of the most prominent xenobiotic metabolic enzymes. It can catalyze the conversion of heteroatom-containing chemicals to polar, readily excretable metabolites and is considered an efficient detoxification system for xenobiotics. Bivalves can accumulate paralytic shellfish toxins (PSTs) produced by dinoflagellates, especially during outbreaks of harmful algal blooms. Exploring FMO genes in bivalves may contribute to a better understanding of the adaptation of these species and the mechanisms of PSTs bioavailability. Therefore, through genome screening, we examined the expansion of FMO genes in two scallops ( Patinopecten yessoensis and Chlamys farreri ) and found a new subfamily (FMO_like). Our expression analyses revealed that, in both scallops, members of the FMO_N-oxide and FMO_like subfamilies were mainly expressed from the D-stage larvae to juveniles, whereas the FMO_GS-OX subfamily genes were mainly expressed at and prior to the trochophore stage. In adult organs, higher expressions of FMO s were observed in the kidney and hepatopancreas than in other organs. After exposure to PST-producing algae, expression changes in FMO s occurred in hepatopancreas and kidney of both scallops, with more members being up-regulated in hepatopancreas than in kidney for Alexandrium catenella exposure, while more up-regulated FMO s were found in kidney than in hepatopancreas of C. farreri exposed to A. minutum . Our findings suggest the adaptive functional diversity of scallop FMO genes in coping with the toxicity of PST-producing algae.

LRP10 Mutations May Correlate with Sporadic Parkinson’s Disease in China - Quanzhen Zhao; Pingping Ning; Xinglong Yang; Changhe Shi; Yuming Xu; Qiuyan Shen; Hongyan Huang; Dan Xie; Yalan Chen; Yanming Xu (Molecular Neurobiology, 2021)

An effective method for identification of three mussel species and their hybrids based on SNPs - Xingqiang Chen; Ronghua Li; Chunlin Wang; Changkao Mu; Weiwei Song; Lei Liu; Ce Shi; Pingping Zhan (Conservation Genetics Resources, 2020)

Colon-Targeted Delivery of IgY Against Clostridium difficile Toxin A and B by Encapsulation in Chitosan-Ca Pectinate Microbeads - Pingping Xing; Yanan Shi; Chuangchuang Dong; Hong Liu; Yan Cheng; Junbo Sun; Dalei Li; Min Li; Kaoxiang Sun; Dongxiao Feng (AAPS PharmSciTech, 2017)

Moisture Adsorption Isotherms and Thermodynamic Properties of Penaeus vannamei Meat with and without Maltodextrin Addition - Qilong Shi; Wenwen Lin; Ya Zhao; Pingping Zhang; Ruiying Wang (Journal of Aquatic Food Product Technology, 2016)

Bioactive cyclolanstane-type saponins from the stems of Astragalus membranaceus (Fisch.) Bge. var. mongholicus (Bge.) Hsiao - Tingting Wang; Jingya Ruan; Xiaoxia Li; Liping Chao; Pingping Shi; Lifeng Han; Yi Zhang; Tao Wang (Journal of Natural Medicines, 2016)

Downregulation of the lycopene ε-cyclase gene confers tolerance to salt and drought stress in Nicotiana tabacum - Yanmei Shi; Pingping Liu; Yuzhen Xia; Pan Wei; Wenzheng Li; Wei Zhang; Xia Chen; Peijian Cao; Yalong Xu; Lifeng Jin; Feng Li; Zhaopeng Luo; et al. (Acta Physiologiae Plantarum, 2015)

Household pesticide exposure and the risk of childhood acute leukemia in Shanghai, China - Yan Zhang; Yu Gao; Rong Shi; Didi Chen; Xiaojin Wang; Michihiro Kamijima; Kiyoshi Sakai; Tamie Nakajima; Md. Khalequzzaman; Yijun Zhou; Ying Zheng; Pingping Bao; et al. (Environmental Science and Pollution Research, 2015)

PI3K/Akt/uncoupling protein 2 signaling pathway may be involved in cell senescence and apoptosis induced by angiotensin II in human vascular endothelial cells - Ping Li; Xin Guo; Pingping Lei; Shoujun Shi; Shike Luo; Xiaoshu Cheng (Molecular Biology Reports, 2014)